Experimental Verification of Low-Pressure Kinetics Model for Direct Synthesis of Dimethyl Carbonate Over CeO2 Catalyst - G. Ibrahim (7601063) (2024)
Dimethyl carbonate (DMC) has emerged as a promising candidate for sustainable chemical processes due to its remarkable versatility and low toxicity. From a green chemistry perspective, the direct synthesis of DMC has been considered the most promising route, as water is the only byproduct generated in the reaction between CO2 and methanol. However, this synthetic route has faced significant thermodynamic limitations, even at elevated pressure conditions. Therefore, a two-part study explored low-pressure synthesis of DMC via the direct route, and a low-pressure kinetic model for the CeO2 catalyst was developed based on the results. Proposed Langmuir–Hinshelwood mechanisms were verified using experimental data generated in our labs. The investigation suggests that DMC formation in the direct synthetic route is a surface reaction of CO2 and methanol on the catalyst. The kinetic model predictions closely aligned with experimental data, demonstrating a 17% mean absolute percentage error and indicating a high level of predictability. Additionally, a rigorous assessment was conducted on CO2 fixations in DMC synthesis, quantifying CO2 capture and its conversion into stable or high-value products, formally designated as CO2 Fixation (CO2Fix). The CO2Fix analysis revealed that, at a conversion rate of 27%, the process can achieve a "net zero" state when operated at an approximate pressure of 30 bar, thereby supporting the viability of low-pressure synthesis. Increasing the conversion rate to levels exceeding 95% significantly enhances the CO2Fix metric, potentially surpassing 3.5 or higher. Other Information Published in: Topics in Catalysis License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11244-024-02003-w